Educational innovation for infection control in Tanzania: bridging the policy to practice gap. Issue 3 (May 2014) - Jones, Mark; Whitfield, Ann; Thomas, Susan; Gower, Shelley; Michael, Rene
The incidence of hospital acquired infection in developing countries is between two to 20 times higher than in developed countries and is attributable to multiple causes. Evidence-based international policies and guidelines developed to improve infection prevention and control are often not used in practice in these countries. To combat this challenge, this article presents an innovative educational framework used to bridge the gap between policy written by global health agencies and the realities of practice in Tanzania.